Compact Amplitude-Monopulse Antenna for Joint Two-Dimensional Direction Finding and Sectorized Communications in the 2.4 GHz ISM Band - Miguel Poveda-Garcia; Jose Antonio Lopez-Pastor; Maria Campo-Valera; Alejandro Gil-Martinez; David Canete-Rebenaque; Jose Luis Gomez-Tornero (IEEE Open Journal of Antennas and Propagation)
A compact antenna design is proposed to synthesize two-dimensional amplitude monopulse radiation patterns, with application to integrated sensing and communications in the ISM 2.4 GHz band. The antenna makes use of two air-filled leaky waveguides to generate four diagonally scanned beams without the need of complex feeding networks. The design demonstrates the generation of monopulse patterns in the two perpendicular planes of the antenna, covering an angular field of view of 40° X 60° where the Direction of Arrival can be estimated. The simple structure and compactness of this antenna makes it very suitable for low-cost multi-functional joint radar-communications using commercial wireless networks.